The effectiveness of sputum pH analysis in the prediction of response to therapy in patients with pulmonary tuberculosis - Masuda, Makoto; Sato, Takashi; Sakamaki, Kentaro; Kudo, Makoto; Kaneko, Takeshi; Ishigatsubo, Yoshiaki (PeerJ, 2015)
Purpose. The predictive factor of response to antituberculous therapy has not been fully elucidated. Airway acidity has been thought to be a potential indicator of the bactericidal activity. Therefore, we hypothesized that monitoring airway acidity by measuring sputum pH could predict response to therapy. Methods. A total of 47 patients having newly diagnosed, smear-positive, active pulmonary tuberculosis were enrolled between October 2011 and March 2014. Sputum samples were serially analyzed before and after treatment. Eligible patients who initiated a standard 6-month treatment were monitored for the length of time to sputum smear and culture conversion. Results. There were 39 patients who completed a 2-month intensive phase of isoniazid, rifampicin, pyrazinamide, and ethambutol therapy followed by a 4-month continuation phase of isoniazid and rifampicin. Although factors including age, cavitation, sputum grade, and use of an acid-suppressant were associated with initial low sputum pH in univariate analysis, multivariate analysis revealed that only age ≥61 years was a statistically important factor predicting low pH value (p = 0.005). Further outcome analysis showed that initial low sputum pH before treatment was the only factor significantly associated with shorter length of time to both sputum smear and culture conversion (p = 0.034 and 0.019, respectively) independent of the effects of age, sputum bacterial load, extent of lung lesion, and cavitation. Thus, initial low sputum pH indicated favorable response to anti-tuberculosis therapy. Conclusions. Measuring sputum pH is an easy and inexpensive way of predicting response to standard combination therapy in patients with pulmonary tuberculosis.
Keywords: Antituberculous therapy; Pulmonary tuberculosis; Airway acidity; Sputum pH